Implications of Investment Policy on Legal Certainty of Community Land Rights - Isnaini, Isnaini (Fakultas Syariah INSURI Ponorogo, 2025)
This study aims to analyze the implications of investment policy on the legal certainty of people's land rights in Indonesia. Although investment is seen as a strategic instrument to encourage economic growth, government policies such as the Investment Law Number 25 of 2007 and the Job Creation Law often cause disharmony with the Basic Agrarian Law Number 5 of 1960. Through a normative juridical approach, this study examines the relationship between investment regulation and land rights protection, particularly in the context of agrarian conflicts that arise from overlapping authority, weak recognition of customary rights, and the unclear status of land law. The findings indicate that investment policy implementation often prioritizes the interests of investors over those of local communities, thereby increasing the potential for evictions, land disputes, and legal uncertainty. The case of Rempang Island and plantations in West Kalimantan confirms that inconsistent regulations contribute to the marginalization of society. This study recommends harmonizing regulations, strengthening conflict resolution mechanisms, and reforming land law to ensure a balance between economic interests and the protection of people's rights.